2019
DOI: 10.1111/acps.13127
|View full text |Cite
|
Sign up to set email alerts
|

World Trade Center exposure, post‐traumatic stress disorder, and subjective cognitive concerns in a cohort of rescue/recovery workers

Abstract: Objective To determine whether World Trade Center (WTC)‐exposure intensity and post‐traumatic stress disorder (PTSD) are associated with subjective cognitive change in rescue/recovery workers. Method The population included 7875 rescue/recovery workers who completed a subjective cognition measure, the Cognitive Function Instrument (CFI), between 3/1/2018 and 2/28/2019 during routine monitoring, indicating whether they had experienced cognitive and functional difficulties in the past year. Higher scores indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Recent data from the Centers for Disease Control and Prevention (CDC) show that the prevalence of self-reported worsening confusion or memory loss in the past 12 months in US adults aged 45 years and older is between 11–12% [ 5 ]. Previously, we reported that exposure to the World Trade Center (WTC) disaster site, post-traumatic stress disorder (PTSD) symptoms, and depressive symptoms were associated with subjective cognitive concerns in Fire Department of the City of New York (FDNY) rescue/recovery workers [ 6 ]. Our findings were consistent with those from a study of non-FDNY WTC responders, which reported that WTC exposure and PTSD symptoms were associated with worse performance on an objective cognitive measure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from the Centers for Disease Control and Prevention (CDC) show that the prevalence of self-reported worsening confusion or memory loss in the past 12 months in US adults aged 45 years and older is between 11–12% [ 5 ]. Previously, we reported that exposure to the World Trade Center (WTC) disaster site, post-traumatic stress disorder (PTSD) symptoms, and depressive symptoms were associated with subjective cognitive concerns in Fire Department of the City of New York (FDNY) rescue/recovery workers [ 6 ]. Our findings were consistent with those from a study of non-FDNY WTC responders, which reported that WTC exposure and PTSD symptoms were associated with worse performance on an objective cognitive measure [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, our sample was chosen to encompass a middle-aged group of enrollees, so those in our sample were unlikely to suffer from dementia, which could lead to misclassification in reporting of CML. Further, a recent study of the association between 9/11 exposure and 9/11-related PTSD and changes in self-reported cognitive function using the Cognitive Function Instrument (CFI) [ 48 ] demonstrated results that were comparable with those from a recent study that used objective measures of cognitive function [ 35 ]. Furthermore, social desirability bias could lead to under-reporting of CML; similar under-reporting could occur for mental health conditions and symptoms.…”
Section: Discussionmentioning
confidence: 91%
“…There is growing evidence of early onset cognitive impairment in the WTC-exposed population [ 148 , 149 , 150 , 151 ]. Two causal pathways have been suggested for exposure-related disease.…”
Section: Research Portfoliomentioning
confidence: 99%
“…There is mounting evidence from human and animal studies indicating that inhalation of air pollutants can increase the risk of neurodegenerative diseases, including cognitively impairing diseases [ 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ]. Exposure–response associations between proxies of WTC dust exposure and measures of cognitive impairment have been observed [ 148 ]. For example, WTC first responders with high-intensity exposures were more likely to report subjective cognitive deficits compared to responders with lower-level WTC exposure [ 148 ].…”
Section: Research Portfoliomentioning
confidence: 99%
See 1 more Smart Citation